The Oxford handbook of business groups - Colpan, Asli M.; Hikino, Takashi; Lincoln, James R. (Oxford : Oxford University Press, 2010)
This handbook provides a comprehensive analysis of business groups around the world. It focuses on the adaptive and competitive capabilities of business groups and their evolutionary dynamics, as well as considering the historical and theoretical contexts of business groups.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Conglomerate corporations; Business networks